2020
DOI: 10.3390/molecules25163648
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities and Volatile Flavor Components of Selected Single-Origin and Blend Chocolates

Abstract: The biological activity of chocolates gains more and more attention of consumers. Its antioxidant properties depend, among other factors, mainly on the origin of cocoa and the characteristics that this origin gives to the final product. Therefore, the aim of the study was to measure and compare the total content of polyphenols, antioxidant activity, and key odorants of commercial chocolates made from blend cocoa with single-origin ones. The highest content of polyphenols was found in 90% blend cocoa chocolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
(48 reference statements)
2
16
1
Order By: Relevance
“…Belščak-Cvitanović et al [ 14 ] reported TPC content of approximately 3.5–5.5 mg GAE/g of defatted sample for milk chocolate and approximately 7.5–12 mg GAE/g of defatted sample for dark chocolate. Godočikova et al [ 15 ] reported TPC values of 4.83–23.58 g GAE/kg of defatted sample. In both these researches the standard Folin-Ciocalteu method was applied, corresponding to our results presented as TPC1 in Table 2 , which ranged from 1.70 to 3.63 mg GAE/g of defatted sample for milk and 7.54–12.71 mg GAE/g of defatted sample for dark chocolates.…”
Section: Resultsmentioning
confidence: 99%
“…Belščak-Cvitanović et al [ 14 ] reported TPC content of approximately 3.5–5.5 mg GAE/g of defatted sample for milk chocolate and approximately 7.5–12 mg GAE/g of defatted sample for dark chocolate. Godočikova et al [ 15 ] reported TPC values of 4.83–23.58 g GAE/kg of defatted sample. In both these researches the standard Folin-Ciocalteu method was applied, corresponding to our results presented as TPC1 in Table 2 , which ranged from 1.70 to 3.63 mg GAE/g of defatted sample for milk and 7.54–12.71 mg GAE/g of defatted sample for dark chocolates.…”
Section: Resultsmentioning
confidence: 99%
“…This is demonstrated by the fruit pulp turning into a liquid and draining away, which enhances aeration and causes acetic acid bacteria to convert alcohol to acetic acid. The pH of cocoa beans is lowered by acetic acid to between 4.5 and 5.5; the temperature rises to 45-50 • C and the cell walls of the cacao seed become permeable; and an oxidative process takes control of the entire mass, triggering the growth of lactic bacteria, allowing for enzymatic reactions and subsequent fermentation [15,16]. Then, phenolic compound condensation and oxidation processes become the focus.…”
Section: Fermentation Stage Of Cocoa Manufacturingmentioning
confidence: 99%
“…It was discovered that temperatures over 130 • C and a roasting time over 25 min had a positive impact on the concentration of all methylpyrazines [17,23]. The rapid drying of cocoa beans, on the other hand, traps volatile acids inside the beans, which is undesirable because the high acid concentration can result in an off-putting aroma of both cocoa and chocolate [15].…”
Section: Roasting Stage Of Cocoa Manufacturingmentioning
confidence: 99%
“…Other recent studies have observed the effects of cocoa on the intestinal microbiota composition, which in turn have been linked to an improved glucose homeostasis and gut health 80–82 . Most publications linked those cocoa benefits to phenolic acids, and particularly flavanol composition, compounds that have been found to be dependent on cocoa origin 83 . But also, some works have associated bioactive properties with oligopeptides from artisanal fermented cocoa 84 …”
Section: Nutraceutical Properties and Human Healthmentioning
confidence: 99%